2000
DOI: 10.1111/j.0014-3820.2000.tb00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Excursions on Adaptive Landscapes: Density-Dependent Selection on Egg Size

Abstract: Theories of density-dependent natural selection suggest that intraspecific competition will favor juveniles of high competitive ability. Empirical evidence has been provided from laboratory selection experiments, but field studies are lacking due to the logistical difficulties of experimentally manipulating population densities in natural settings. Here, we present data from a decade-long experimental field study of side-blotched lizards, Uta stansburiana that overcomes these difficulties. We tested the hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 43 publications
6
78
0
Order By: Relevance
“…Females on high-quality territories laid their eggs an average of 5.7 days earlier than females on low-quality territories [ANOVA, F(1,13) ϭ 5.36, P ϭ 0.03], thereby increasing the likelihood that they would produce additional clutches of eggs (25) and their progeny would compete successfully and survive better than progeny that were laid later in the season (26). Females on high-quality territories also produced larger eggs for both sons and daughters than did females on low-quality territories [analysis of covariance for sons egg mass, F(1,11) ϭ 4.97, P ϭ 0.04, covariate for mother's mass P ϭ 0.09; for daughters egg mass, F(1,11) ϭ 7.25, P ϭ 0.02, covariate for mother's mass P ϭ 0.14; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Females on high-quality territories laid their eggs an average of 5.7 days earlier than females on low-quality territories [ANOVA, F(1,13) ϭ 5.36, P ϭ 0.03], thereby increasing the likelihood that they would produce additional clutches of eggs (25) and their progeny would compete successfully and survive better than progeny that were laid later in the season (26). Females on high-quality territories also produced larger eggs for both sons and daughters than did females on low-quality territories [analysis of covariance for sons egg mass, F(1,11) ϭ 4.97, P ϭ 0.04, covariate for mother's mass P ϭ 0.09; for daughters egg mass, F(1,11) ϭ 7.25, P ϭ 0.02, covariate for mother's mass P ϭ 0.14; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Side-blotched lizards, U. stansburiana, are small (7-10 g) lizards that mature 1 year after hatching, and most adults survive only 1 season of reproduction. In our study area in the Coast Range of central California, adult population densities in certain years may approach 800 per hectare and juvenile densities 2,600 per hectare, which is probably among the highest for terrestrial vertebrate populations (11). As part of our long-term population studies (14), we captured and observed lizards during the reproductive seasons (late February to August) of 1998 and 1999.…”
Section: Methodsmentioning
confidence: 99%
“…Eggs obtained from the dams were incubated in a common laboratory environment with temperature and hydric conditions carefully controlled until hatching (7,11). Incubation in this common laboratory environment controlled for maternal effects in the field because of differences in oviposition sites between This paper was submitted directly (Track II) to the PNAS office.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations